Rheological Behavior of Gassy Marine Clay: Coupling Effects of Bubbles and Salinity - Zhuanzhuan Zhang; Xionghuan Tan; Lizhong Wang; Gang Cao; Yuan Lin; Yi Hong (Journal of Marine Science and Engineering)
Understanding the rheological behavior of marine clay is crucial to analyzing submarine landslides and their impact on marine resource exploitation. Dispersed bubbles in marine clay (gassy clay) and electrolytes in seawater (e.g., NaCl concentration of 0.47 M) significantly impacts rheological properties. Under low ionic strength and low pore water pressure conditions, dispersed bubbles have a strengthening effect on the yield stress and the viscosity of clays. This effect turns into a weakening effect when the pore water pressure reaches 300 kPa or the ionic strength exceeds 0.18 M. It was proposed that the effect of bubbles, whether strengthening or weakening, was determined by the size of bubbles with respect to the characteristic size of the particle structure formed by clay particles. A theoretical model was developed, which reasonably captures rheological behaviors of gassy clays.